The Conserved Endoribonuclease YbeY Is Required for Chloroplast Ribosomal RNA Processing in Arabidopsis. Issue 1 (25th March 2015) - Liu, Jinwen; Zhou, Wenbin; Liu, Guifeng; Yang, Chuanping; Sun, Yi; Wu, Wenjuan; Cao, Shenquan; Wang, Chong; Hai, Guanghui; Wang, Zhifeng; Bock, Ralph; Huang, Jirong; et al.
Abstract : The Arabidopsis endoribonuclease YbeY is required for chloroplast rRNA processing, and its deficiency reduces chloroplast activity and normal plant growth. Abstract: Maturation of chloroplast ribosomal RNAs (rRNA s) comprises several endoribonucleolytic and exoribonucleolytic processing steps. However, little is known about the specific enzymes involved and the cleavage steps they catalyze. Here, we report the functional characterization of the single Arabidopsis ( Arabidopsis thaliana ) gene encoding a putative YbeY endoribonuclease. AtYbeY null mutants are seedling lethal, indicating that AtYbeY function is essential for plant growth. Knockdown plants display slow growth and show pale-green leaves. Physiological and ultrastructural analyses of atybeY mutants revealed impaired photosynthesis and defective chloroplast development. Fluorescent microcopy analysis showed that, when fused with the green fluorescence protein, AtYbeY is localized in chloroplasts. Immunoblot and RNA gel-blot assays revealed that the levels of chloroplast-encoded subunits of photosynthetic complexes are reduced in atybeY mutants, but the corresponding transcripts accumulate normally. In addition, atybeY mutants display defective maturation of both the 5′ and 3′ ends of 16S, 23S, and 4.5S rRNA s as well as decreased accumulation of mature transcripts from the transfer RNA genes contained in the chloroplast rRNA operon. Consequently, mutant plants show a severe deficiency in ribosome biogenesis, which, in turn, results in impaired plastid translational activity. Furthermore, biochemical assays show that recombinant AtYbeY is able to cleave chloroplast rRNA s as well as messenger RNAs and transfer RNAs in vitro. Taken together, our findings indicate that AtYbeY is a chloroplast-localized endoribonuclease that is required for chloroplast rRNA processing and thus for normal growth and development.